Professional health regulation in the public interest : international perspectives - Chamberlain, John Martyn, 1972-; Dent, Mike, 1944-; Saks, Mike (Policy Press, 2018)
Bringing together leading academics worldwide, this collection compares and critically examines the ways in which different countries are regulating healthcare in general, and health professions in particular, in the interest of users and the wider public.
Keywords: Medical care -- Standards.; Medical personnel.; Medical policy.; Medical care -- Quality control.; Health Policy; Delivery of Health Care -- standards; Health Personnel -- standards; Quality Assurance, Health Care; Professionalism; Personnel médical.; Politique sanitaire.; Soins médicaux -- Qualité -- Contrôle.; Soins médicaux -- Normes.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; Medical policy; Medical care -- Quality control; Medical care -- Standards; Medical personnel; Electronic book.